Hasil Prevalensi Sifilis Reaktif Metode Chlia dalam Donor Darah UDD PMI Lombok Barat - Rina Puspita; Yuli Arinta Dewi; Laela Kanaya (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2021)
Background: Syphilis is a chronic and systematic disease caused by Treponema Pallidum. Syphilis transmission through sexual intercourse, can also occur vertivally ftom mother to fetus in the womb or at birt, through blood products and sometimes also transmitted through medical devices. WHO estimates that more than one million people worldwide diagnosed with Sexually Transmitted Diseases every day. Method: The research is a descriptive survey with Cross Sectional design. The data is taken from West Lombok Indonesian Red Cross Blood Donor Unit screening laboratory of period 2020. Result : The data showed the amount of syphilis reactive donors are as many as 36 people. The data showed the highest cases among blood dorors are of the age group 40-50 years as many as 12 people or 33,3% of the total syphilis reactive donors with the most cases only being male as many as 36 people or 100% of the total syphilis reactive blood donors. Implication : Theimplication of this study are: First, prevention efforts against risky sexual behavior so that the incidence of syphilis may decrease. Second, reduce the risk of transmission of sexually transmitted diseases through blood transfusions Novelty: The study was conducted to determine the prevalence of syphilis examination results in blood donors at UDD PMI west Lombok in 2020